LAYANAN KONSELING INDIVIDUAL PADA WARGA BINAAN REHABILITASI NARKOBA DI RUTAN KELAS I MAKASSAR - Surya Algazali Akbar; Cindy Caroline; Misly Megautari; Perdana Kusuma (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2022)
Abstract : The inmates are small groups in the community that are housed in the State Detention Center. The inmates themselves are people who commit criminal offenses and are waiting for the trial process. One of the detention centers where individual counseling is carried out is the Makassar Class I Rutan. There are various criminal cases that have been committed by the inmates that have resulted in red cells. However, detainees in the Makassar Class I Rutan are dominated by inmates who are caught in drug abuse cases. Based on the data obtained from interviews in the field, it was recorded that 70% of the inmates in the Makassar Class I Rutan were entangled in drug cases. Therefore, this individual counseling activity is carried out as assistance in the rehabilitation process so that the inmates who are participants in this activity can become positive individuals, can motivate and return to their normal life and can plan their actions and life goals. Each counseling participant has as many as 3 meeting sessions and is carried out for 3 weeks. The skills used during this counseling session are active listening, attending behavior, and paraphrasing. In addition, participants as clients in this counseling activity are also given treatment planning so that participants in this counseling activity are able to plan actions and be independent in making decisions and future goals. After the implementation of this activity, participants as clients feel positive energy in themselves and feel more motivated to become a better person in the future.